INFLUENCE OF NOZZLE TYPE, WORKING PRESSURE, AND THEIR INTERACTION ON DROPLETS QUALITY USING KNAPSACK SPRAYER - Alheidary, M. H. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The present experiment was carried out at the Dept. of Agricultural Machines and Equipment, College of Agriculture, University of Basrah. The aim of the study is to highlight the effect of the nozzle type, working pressure and their interaction onto droplet quality using knapsack sprayer to improve their performance. Droplet characteristics were sampled on white paper cards at different distances from the nozzle. On the samples spray deposits, spray coverage, droplet size, and volume median diameter was measured using BSF tracer with water after their deposit on the sample. The main studied parameters were: Six nozzle types hollow cone, Flat fan ceramic, flat fan ISO, CFA, AirMix and flat fan air induction nozzle. Two working pressures were 15 and 25 psi. All measurements carried out at the same nozzle height of 50cm by using CRD with three replications. The main results of this study showed the best spray deposition and spray coverage with the highest values 0.06nµl.cm-2 and 63% respectively when hollow cone nozzle was compared to other nozzles under the same operating conditions. Whereas, the Flat fan air induction nozzle appeared the most significant droplet size and VMD 377.69 µm and 378 µm respectively when it was compared to the hollow cone and flat fan nozzles.